2019
DOI: 10.3390/su11030570
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Environmental Amenities in Peri-Urban Areas: Evidence from Poland

Abstract: Ecosystems provide services that contribute to the well-being of people living within a city’s borders and on the urban–rural fringe. While benefits from green areas in urban settings are well investigated, peri-urban areas are significantly less addressed by researchers than cities. This study aims to evaluate the importance of environmental amenities in peri-urban areas using the hedonic pricing method to assess people’s willingness to pay for environmental goods and services. A local regression model (geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 64 publications
2
15
0
4
Order By: Relevance
“…Hence, the evidence presented here is important, as it highlights a statistically significant relationship between the price of land and the distance to the nearest forest and PNA. However, although significant, the regression coefficients have values close to zero, which means that buyers are aware of but rather indifferent to environmental features in this informal market, in contrast with formal housing markets elsewhere (Morancho, 2003;Saphores and Li, 2012;Sylla et al, 2019). Even in formal markets in developing countries, environmental quality has a large impact on property prices, as reported by Humavindu and Stage (2003) for Namibia.…”
Section: Environmental Variablesmentioning
confidence: 79%
“…Hence, the evidence presented here is important, as it highlights a statistically significant relationship between the price of land and the distance to the nearest forest and PNA. However, although significant, the regression coefficients have values close to zero, which means that buyers are aware of but rather indifferent to environmental features in this informal market, in contrast with formal housing markets elsewhere (Morancho, 2003;Saphores and Li, 2012;Sylla et al, 2019). Even in formal markets in developing countries, environmental quality has a large impact on property prices, as reported by Humavindu and Stage (2003) for Namibia.…”
Section: Environmental Variablesmentioning
confidence: 79%
“…The research studies on green spaces in Poland cover quantitative studies in the country and in selected cities [47][48][49] as well as spatial analyses related to the accessibility of green spaces [16,17,30,[50][51][52]. Other presented research studies concern ecosystem services [53], allotment gardens [33,34,54], urban planning [55], the management strategy of the Białowieża Forest [56] and the influence of the vicinity of greenery on housing prices [57,58]. The publication [15] discusses the implementation of urban environmental justice in post-socialist cities (also in Poland).…”
Section: Literature Studiesmentioning
confidence: 99%
“…Dawes et al [16] showed that urban areas reforested through a state program in Florida did not necessarily spatially overlap with areas where demand was for tree-related ES. Sylla et al [42] illustrated how to avoid spatial mismatches between the spatial units used in research and the ones municipal policies work in. Both papers indicate a need to coordinate better between policies and other aspects of society such as demand or research.…”
Section: Spatial Mismatchesmentioning
confidence: 99%